Cyclic poly(β-amino ester)s with enhanced gene transfection activity synthesized through intra-molecular cyclization. Issue 13 (18th January 2022) - Wang, Chenfei; Huang, Xiaobei; Sun, Litao; Li, Qiuxia; Li, Zhili; Yong, Haiyang; Che, Delu; Yan, Cong; Geng, Songmei; Wang, Wenxin; Zhou, Dezhong
Abstract : Cyclic poly(β-amino ester)s (CPAEs) are synthesized via sequential Michael addition and free radical initiating ring-closure reaction, and show superior gene transfection compared to their linear counterparts. Abstract : Topological structure plays a critical role in gene delivery of cationic polymers. Cyclic poly(β-amino ester)s (CPAEs) are successfully synthesized via sequential Michael addition and free radical initiating ring-closure reaction. The CPAEs exhibit superior gene transfection efficiency and safety profile compared to their linear counterparts.